2013
DOI: 10.1292/jvms.12-0245
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Gα<i><sub>i2</sub></i>-Expressing Axon Terminals in the Goat Main Olfactory Bulb

Abstract: ABSTRACT. In rodents, Gα i2 -expressing sensory neurons (SNs) that co-express vomeronasal receptor type 1 (V1R) are specifically found in the vomeronasal organ (VNO) and project their axons to the accessory olfactory bulb (AOB). In goats, however, Gα i2 /V1R-expressing SNs exist in both the VNO and the olfactory epithelium. Thus, we examined whether the Gα i2 -expressing axons functionally project to the main olfactory bulb (MOB). We analyzed the expression of Gα i2 in the olfactory bulb and found small Gα i2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, a study using larger animals, such as goats, indicated that glomeruli are absent in part of the olfactory bulb surface (Ohara et al, 2013). Surface areas containing glomeruli may actually be more related to the number of glomeruli than to olfactory bulb volume.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study using larger animals, such as goats, indicated that glomeruli are absent in part of the olfactory bulb surface (Ohara et al, 2013). Surface areas containing glomeruli may actually be more related to the number of glomeruli than to olfactory bulb volume.…”
Section: Discussionmentioning
confidence: 99%
“…Although the structure of the sheep nasal cavity is fairly similar to that in rodents [ 3 ], both the distribution of the OE in the nasal cavity and the zonal organization of the OE still have not been investigated in ungulates. Among ungulates, the goat olfactory system has been extensively characterized [ 15 , 16 , 22 , 23 ]. Moreover, the goat olfactory system is equipped with a unique subset of OSNs that express both vomeronasal type-1 receptor (V1rs) and Gαi2, a V1rs-associated G protein [ 23 ].…”
mentioning
confidence: 99%